Phytochemical Analysis and in Vitro Assessment of Antimicrobial Activity of Olea Europaea Leaf Extract - Oubaid, Enass Najem (American Journal of Biomedicine and Pharmacy, 2025)
Background: Olea europaea leaves are rich in phenolic acids, flavonoids, steroids, terpenoids. These phytochemicals are known for their anti-inflammatory, antioxidant and antimicrobial properties. Objectives: this study is designed to explore the phytochemical compounds in Olea europaea leaves extract and to evaluate the antimicrobial activity of it against pathogenic bacteria. Materials and methods: Extracts of Olea europaea first examined for their phytochemical constituents using standard preliminary screening tests. In addition, the antimicrobial activity of different concentrations of olive tree extract (10%, 20%, 30%, and 40%) was evaluated against four bacterial isolates against- Staphylococcus aureus, Enterococcus ssp., Escherichia coli, and Klebsiella ssp. in vitro. The assessment was carried out using the agar well diffusion method, with levofloxacin disc used as a reference control for comparison. Results: the results of phytochemical analysis for the hydroethanolic extract of Olea europaea detected the presence of terpenoids, alkaloids, polyphenols, and flavonoids, while saponins were absent. The hydroethanolic extract of Olea europaea showed dose-dependent antimicrobial activity against the tested microorganisms, with greater inhibitory effects observed at higher extract concentrations. Conclusion: the finding of this study showed that Olea europaea leaf extract exhibited antimicrobial activity in a dose dependent manner.